2003
DOI: 10.1097/01.asn.0000047560.51444.3a
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Myocardial Perfusion Studies in Patients with End-Stage Renal Disease Assessed for Kidney or Kidney-Pancreas Transplantation

Abstract: Abstract. The prognostic utility of myocardial perfusion studies (MPS) such as thallium scintigraphy and dobutamine stress echocardiography (DSE) for stratifying cardiac risk among candidates for kidney or kidney-pancreas transplantation is uncertain. This study is a meta-analysis to determine the prognostic significance of MPS results on future myocardial infarction (MI) and cardiac death (CD) in patients with end-stage renal disease (ESRD) assessed for kidney or kidney-pancreas transplantation. MEDLINE was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(77 citation statements)
references
References 36 publications
3
70
0
4
Order By: Relevance
“…A recent meta-analysis reveals that stress imaging is of value in predicting CVD morbidity and mortality in kidney transplantation candidates treated by dialysis. 32 It remains unknown, however, whether the diagnostic accuracy of these tests, as defined by a "gold standard" of angiographic obstructive coronary artery disease, is different from the general population. Furthermore, it remains unknown whether stress nuclear or stress echocardiographic testing is more accurate in patients with CKD.…”
Section: Spectrum Of Cvd In Ckd and Differences From The General Popumentioning
confidence: 99%
“…A recent meta-analysis reveals that stress imaging is of value in predicting CVD morbidity and mortality in kidney transplantation candidates treated by dialysis. 32 It remains unknown, however, whether the diagnostic accuracy of these tests, as defined by a "gold standard" of angiographic obstructive coronary artery disease, is different from the general population. Furthermore, it remains unknown whether stress nuclear or stress echocardiographic testing is more accurate in patients with CKD.…”
Section: Spectrum Of Cvd In Ckd and Differences From The General Popumentioning
confidence: 99%
“…[2][3][4] Studies evaluating the prognostic value of MPS have not included renal dysfunction in their analyses 20 or have only included patients with end-stage renal disease who are renal transplant candidates. [21][22][23] Hence, our objectives were severalfold: (1) to study the prognostic value of myocardial perfusion abnormalities on single-photon emission CT (SPECT) in the risk stratification of patients with varying degrees of renal dysfunction; (2) to study the impact of renal dysfunction on cardiovascular outcomes in patients undergoing MPS for evaluation of CAD; and (3) to determine whether renal dysfunction (estimated glomerular filtration rate [eGFR] Ͻ60 mL · min Ϫ1 · 1.73 m Ϫ2 ) combined with myocardial perfusion abnormalities on MPS (summed stress score [SSS]) provides additional prognostic information superior to either marker alone.…”
mentioning
confidence: 99%
“…We wondered whether this finding might indicate the presence of coronary artery disease with silent myocardial ischemia, and therefore decided to investigate these patients further using a test capable of detecting the presence of an ongoing reversible myocardial ischemia such as dipyridamoleexercise (D-E) thallium scintigraphy. [10][11][12] In a previous study involving asymptomatic HD patients, D-E thallium scintigraphy showed a sensitivity of 92% and a specificity of 89% in detecting significant coronary lesions compared with coronary angiography. [11] Data are mean ± SD.…”
Section: Discussionmentioning
confidence: 93%